Chai-Gui Decoction and its representative components ameliorate spontaneous hypertension rats by modulating lipid metabolism and gut microbiota. (6th April 2023) - Zhu, Hongjun; Xu, Chen; Dong, Yun; Lu, Shu; Guo, Linxiu
Abstract: Ethnopharmacological relevance: Hypertension coincides with the category of "vertigo" and/or "headache" on the basis clinical manifestations and traditional Chinese medicine (TCM) theory. Chai-Gui Decoction (CGD), which is in usage for relieving "vertigo" and/or "headache", had been demonstrated to be useful in ameliorating hypertension. Aim of study: This study was planned to investigate the mechanism of CGD and its components in hypertension by using spontaneous hypertension rat (SHR). Materials and methods: CGD extract and its classification component samples (compounds in plasma, CP; compounds in gut, CG; compounds in plasma and gut, CPG) were prepared for animal experiment. SHR rats were induced with CGD extract (3 g/kg/d BW, 5 g/kg/d BW, 15 g/kg/d BW) and CGD-component classes (CP = 19.501 mg/kg/d, CG = 5.240 mg/kg/d, CPG = 24.741 mg/kg/d) for 4 weeks. Blood pressure (BP) and indexes of renin-angiotensin-aldosterone system (RAAS system) were measured. Histopathology was carried out to assess the efficacy of CGD and its components on aorta tissues. Untargeted metabolomics of lipid from rat serum samples were applied by Ultra-High performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UHPLC-Q-TOF-MS) and chemometric analysis to explore the relationship between metabolic pathways and hypertension. 16S rRNA gene sequencing of rat colon content and bioinformatics analysis were used to characterize the effects of CGD and its components on the gut microbiota composition of SHR rats. Results: CGD and its component mixtures showed antihypertensive effect on SHR rats, decreased the blood pressure and reduced the aortic wall thickness in SHR rats. CGD and its component mixtures could improve the RAAS in SHR rats, including increase the percentage of angiotensin 1-7 (Ang 1–7), decrease the percentage of angiotensin II (Ang II), and decrease the Ang Ⅱ/Ang 1–7 ratio. CGD and its component mixtures could regulate the metabolome in SHR rats, mainly as decreasing the higher serum levels of Lysophosphatidylcholine (LPC) 16: 0, LPC 20: 4, and LPC 22: 6. In addition, bacteria from family S24-7 were negatively correlated with levels of LPE 16:0, LPE 18:0, LPE 18:1, and LPE 18:2. Conclusion: CGD and its component mixtures exhibited antihypertensive effect on SHR rats. The underlying mechanism could be related to modulation on RAAS, LPC metabolism and the bacterial abundance of family S24-7 in gut. Graphical abstract: Image 1 Highlights: CGD and its components mixtures shown in vivo antihypertensive effect on SHRs. CGD and its components mixtures improve indexes of RAAS in SHRs. CGD and its component mixtures regulate the lipid metabolome which related to microbiota from family S24-7 in SHRs.